Geomorphic signal of active faulting at the northern edge of Lut Block: Insights on the kinematic scenario of Central Iran. Issue 1 (8th January 2016) - Calzolari, Gabriele; Della Seta, Marta; Rossetti, Federico; Nozaem, Reza; Vignaroli, Gianluca; Cosentino, Domenico; Faccenna, Claudio
Abstract: Recent works documented Neogene to Quaternary dextral strike‐slip tectonics along the Kuh‐e‐Sarhangi and Kuh‐e‐Faghan intraplate strike‐slip faults at the northern edge of the Lut Block of Central Iran, previously thought to be dominated by sinistral strike‐slip deformation. This work focuses on the evidence of Quaternary activity of one of these fault systems, in order to provide new spatiotemporal constraints on their role in the active regional kinematic scenario. Through geomorphological and structural investigation, integrated with optically stimulated luminescence dating of three generations of alluvial fans and fluvial terraces (at 53, 25, and 6 ka), this study documents (i) the topographic inheritance of the long‐term (Myr) punctuated history of fault nucleation, propagation, and exhumation along the northern edge of Lut Block; (ii) the tectonic control on drainage network evolution, pediment formation, fluvial terraces, and alluvial fan architecture; (iii) the minimum Holocene age of Quaternary dextral strike‐slip faulting; and (iv) the evidence of Late Quaternary fault‐related uplift localized along the different fault strands. The documented spatial and temporal constraints on the active dextral strike‐slip tectonics at the northern edge of Lut Block provide new insights on the kinematic model for active faulting in Central Iran, which has been reinterpreted in an escape tectonic scenario. Key Points: Active right lateral strike‐slip tectonics affects the northern edge of Lut Block Tectonic fingerprint is deciphered from fault‐related ridge geomorphic signal New insights on recent kinematic evolution in Central Iran are provided